MAKNA-MAKNA FIGUR NAGA DALAM SENI ARSITEKTUR BANGUNAN SUCI TRADISIONAL BALI - I Nyoman Widya Paramadhyaksa (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2009)
In Balinese traditional sacred architecture, there were many ornaments which were basically in the form of particular animals and plants. One of the many ornaments is in the figure of serpent. The serpent which was in the figure of a mythological giant snake was related to the function of the building. This study discussed about the symbolic serpent symbolizing the earth or land, water, the river flow, the clouds, the rainbow, and as one part of a chronograph. Keywords: Balinese traditional sacred architecture, serpent figure, symbol, chronograph